Effect of ischaemic brain injury on sexual function in adult mice. Issue 3 (29th August 2016) - Tang, Yaohui; Yuan, Falei; Cai, Beibei; Xia, Weiliang; Wang, Yongting; Yang, Guo-Yuan
Abstract : Objective: Priapism refers to a condition with persistent abnormal erection of the penis, which is usually caused by disease or injury in the brain or spinal cord, or obstruction to the outflow of blood through the dorsal vein at the root of the penis, without sexual desires. The effect of cerebral ischaemia on sexual function is unknown. The aim of this study is to explore whether priapism occurs in adult mice. Furthermore, we examined the relationship between priapism and the region of infarct in the brain. Design: Adult male CD-1 mice who underwent permanent middle cerebral artery occlusion (pMCAO) were closely examined from 2 hours to 14 days postoperation. Results: We found that priapism occurs in ∼80% of the mice with pMCAO, which could persist up to 14 days. Further study has demonstrated that the occurrence of priapism is related to the infarct region: priapism is found only in mice with ischaemic injury extending to the hypothalamus and the hippocampus regions. Conclusion: Our result suggested priapism may be used as a deep brain injury marker for evaluating brain injury in mice after pMCAO.